EU politicization and policy initiatives of the European Commission: the case of consumer policy - Christian Rauh (Journal of European Public Policy, 2019)
European integration is increasingly contested in public. What are the policy consequences of this EU politicization? This article argues that politicization challenges the hitherto often technocratic mode of policy preparation in the European Commission. Increased public attention and contestation render the diffuse public a more relevant stakeholder for Europe's central agenda-setter because future competence transfers to Brussels are more likely to be scrutinized in the public realm. This incentivizes Commission actors to generate widely dispersed regulatory benefits through its policy initiatives, particularly where an initiative covers publicly salient issues. Applying this expectation to 17 European consumer policy initiatives suggests that the Commission orients its policy proposals towards wide-spread consumer interest during periods of high EU politicization and issue salience. However, the mechanism is constrained by internal turf conflicts and anticipated Council preferences. These findings highlight that politicization entails both chances and risks for further, policy-driven integration in Europe.
Keywords: 330; consumer policy; European Commission; European integration; politicization; responsiveness; salience